2012
DOI: 10.26740/jptt.v2n2.p108-120
|View full text |Cite
|
Sign up to set email alerts
|

Studi Kasus Dinamika Emosi Pada Anak Autis

Abstract: This study aimed at exploring the emotional dynamics of children with autistic. A qualitative approach with case study method was employed. Two autistic children with average autism severity in Cita Hati Bunda School and Therapy Center for autistic children Sidoarjo were recruited as participants. Data were collected from interviews, observation, and relevant documents. The Plutchik’s concept of emotion components, namely stimulus event, inferred cognition, physiological arousal, feeling state, impulse to acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Regulasi emosi pada anak-anak Autis biasanya muncul atau bangkit karena peserta didik tidak mampu mengontrol emosi secara langsung namun dinamika emosi yang terjadi pada anak autistik sesungguhnya dipengaruhi terutama oleh faktor situasional (Khoirunnisa & Nursalim, 2012). Hasil penelitian juga menunjukkan bahwa PDBK Autis perlu waktu yang lebih banyak untuk memahami konteks rangsangan/stimulasi yang diberikan guru dan GPK.…”
Section: Perencanaan Dan Organisasi Pdbk Autisunclassified
“…Regulasi emosi pada anak-anak Autis biasanya muncul atau bangkit karena peserta didik tidak mampu mengontrol emosi secara langsung namun dinamika emosi yang terjadi pada anak autistik sesungguhnya dipengaruhi terutama oleh faktor situasional (Khoirunnisa & Nursalim, 2012). Hasil penelitian juga menunjukkan bahwa PDBK Autis perlu waktu yang lebih banyak untuk memahami konteks rangsangan/stimulasi yang diberikan guru dan GPK.…”
Section: Perencanaan Dan Organisasi Pdbk Autisunclassified
“…Children with autism spectrum disorders have emotional characteristics that are unstable, hyperactive or very passive, like to be alone, laugh or giggle for no reason, have tantrums and hurt themselves [32]. Research conducted by Khoirunnisa & Nursalim (2012) found that feelings of fear, irritation, anger, sadness, joy, and affection were felt by children with ASD [33]. Emotions in ASD children can be classified into positive emotions and negative emotions.…”
Section: Resultsmentioning
confidence: 99%
“…Emotions in ASD children can be classified into positive emotions and negative emotions. Positive emotions include happy [34][35], love, miss, and shame [35], while negative emotions include anger, fear [34][35], sad, surprised [35], and irritated [33].…”
Section: Resultsmentioning
confidence: 99%
“…Anak autisme cenderung terisolasi dengan manusia dan masuk dalam dunia respetitiv, aktivitas dan minat obsesif (Setyaningsih, 2016). kadang mereka tidak bisa mengontrol emosinya secara baik (Khoirunnisa & Nursalim, 2012) sehingga dapat mengakibatkan kerugian baik dirinya sendiri maupun orang lain. Identifikasi anak autis sangatlah penting sebagai langkah pencegahan dan pengobatan, dikarenakan jika identifikasi terlambat akan mempersulit proses penyembuhan dan pengobatan.…”
Section: Pendahuluanunclassified